Serangan Penggerek Batang Padi dan Peran Musuh Alami dalam Mengendalikan Populasinya pada Persawahan Tanam Serentak dan Tidak Serentak - WAYAN ADIARTAYASA; I NYOMAN WIJAYA (Fakultas Pertanian Universitas Udayana, 2016)
Paddy Rice Stemborer Attact and The Role of Parasitoid in Control That Population atSimultaneous and Stagered Ricefield. The arrangement of suistable agriculture in Baliwhich appropriate with Bali governments mission : Bali Clean and Green Go to Organic. Theconcept of modern agriculture look like contradiction with the aspects suistainableagriculture. The aspect of cultivation have been done by local agriculture community in Balicall it Subak for many years, but the attack of yellow rice borer still happen, wich adversefarmers side, persist. The efforts control wich has been done, still rely on pesticides, becauseit can give quick effect, but it is not appropriate for suistainable agriculture. The othersolution to solve that issues with the integrated pest management (IPM) as the maincomponent of with is the role parasitoids. The experiment was carried out at simultaneousplanting area (Subak Sidakarya, Denpasar Selatan District) and at staggered planting area(Subak Buaji, Denpasar Timur District). The result of this experiment showed that damageintensity of rice stemborer at simmultaneus planting was lower than at staggered plantingarea. There are four species stemborer at simultaneous planting area and at staggered plantingareas, namely Scirpophaga incertulas, Sesamia inferens, Chilo suppressalis, and Chilopolychrysus. Three kinds of egg parasitoids were found to decrease the population of ricedstemborer. They were Tetrastichus schoenobii, Telenomus rowani and Trichogrammajaponicum.